Teacher competency: Descriptive study of Guru Penggerak - Kinanti Geminastiti Hilmiatussadiah; Eeng Ahman; Disman Disman (Inovasi Kurikulum, 2024)
Teachers must have competence in teaching. There are four competencies that teachers must have, namely pedagogical competence, professional competence, personality competence, and social competence. The Guru Penggerak program is hoped to increase competence in learning activities. This research aims to determine whether there are differences in the competencies of driving and non-moving teachers and describe the indicators of each competency. Based on a questionnaire distributed to students in classes X and XI, the greater pedagogical competence of driving teachers and no-moving teachers is found in the indicator that economics teachers speak politely and politely when delivering learning material, there is an ability to adapt to the surrounding environment, which is the highest average in social competences. The research instrument was given to students taught by Guru Penggerak and non-moving teachers. The results of the research show that for each competency indicator, there are indicators that have the same average value of driving teachers and non-moving teachers, but there are differences in professional, pedagogical, and personality competence between driving teachers and non-moving teachers, while social competence is the same between driving teachers and non-moving teachers.   Abstrak Guru harus memiliki kompetensi dalam mengajar, terdapat empat kompetensi yang harus dimiliki oleh guru yaitu kompetensi pedagogik, kompetensi profesional, kompetensi kepribadian dan kompetensi sosial. Adanya program Guru Penggerak diharapkan dapat meningkatkan kompetensi pada kegiatan pembelajaran. Tujuan dilakukan penelitian ini adalah untuk mengetahui apakah ada perbedaan kompetensi yang dimiliki Guru Penggerak dan bukan Guru Penggerak dan mendeskripsikan indikator dari setiap kompetensi. Instrumen penelitian diberikan kepada siswa yang diajar oleh Guru Penggerak dan bukan Guru Penggerak. Berdasarkan angket yang disebar kepada siswa kelas X dan XI sejumlah 23 pertanyaan tentang kompetensi guru, hasil penelitian menunjukkan kompetensi guru berada pada kategori tinggi, kompetensi profesional yang dimiliki Guru Penggerak dan bukan Guru Penggerak memiliki nilai rata-rata tertinggi pada penguasaan materi nilai rata-rata Kompetensi pedagogik Guru penggerak dan bukan Guru Penggerak yang lebih besar terdapat pada indikator Guru ekonomi berbicara santun dan sopan pada saat menyampaikan materi pembelajaran, terdapat kemampuan beradaptasi dengan lingkungan sekitar merupakan rata-rata tertinggi pada kompetensi sosial. Tetapi terdapat perbedaan kompetensi profesional, pedagogik dan kepribadian antara Guru Penggerak dan bukan Guru Penggerak sedangkan untuk kompetensi sosial sama antara Guru Penggerak dan bukan Guru Penggerak. Kata Kunci: Guru; guru penggerak; kompetensi guru